Exploring the potential of pheophorbide A, a chlorophyll-derived compound in modulating GLUT for maintaining glucose homeostasis - Paul, Saptadipa; Pallavi, Anuma; Gandasi, Nikhil R. (Frontiers in Endocrinology, 2024)
Introduction Pheophorbide A, a chlorophyll-breakdown product, is primarily investigated for its anti-oxidant and anti-inflammatory activity. Recent reports on pheophorbide A have shown its potential in lowering blood glucose levels, thus leading to the exploration of its use in diabetes management. Literature has also shown its effect on enhanced insulin secretion, whereas its mechanism on glucose stimulated insulin secretion (GSIS) in pancreatic β cells remains unexplored. Methods In-silico and in-vitro investigations were used to explore the effect of pheophorbide A on class I glucose transporters (GLUTs). In-silico studies include - Molecular docking studies and stability assessment using GROMACS. In-vitro studies include - MTT assay, Glucose uptake assay, Live-cell imaging and tracking of GLUTs in presence of Pheophorbide A compared to control. Results Molecular docking studies revealed better binding affinity of pheophorbide A with GLUT4 (−11.2 Kcal/mol) and GLUT1 (−10.7 Kcal/mol) when compared with metformin (−5.0 Kcal/mol and −4.9 Kcal/mol, respectively). Glucose levels are largely regulated by GLUTs where GLUT1 is one of the transporters that is ubiquitously present in human β cells. Thus, we confirmed the stability of the complex, that is, pheophorbide A-GLUT1 using GROMACS for 100 ns. We further assessed its effect on a pancreatic β cell line (INS-1) for its viability using an MTT assay. Pheophorbide A (0.1–1 µM) showed a dose-dependent response on cell viability and was comparable to standard metformin. To assess how pheophorbide A mechanistically acts on GLUT1 in pancreatic β cell, we transfected INS-1 cells with GLUT1–enhanced green fluorescent protein and checked how the treatment of pheophorbide A (0.50 µM) modulates GLUT1 trafficking using live-cell imaging. We observed a significant increase in GLUT1 density when treated with pheophorbide A (0.442 ± 0.01 µm−2) at 20 mM glucose concentration when compared to GLUT1 control (0.234 ± 0.01 µm−2) and metformin (0.296 ± 0.02 µm−2). The average speed and distance travelled by GLUT1 puncta were observed to decrease when treated with pheophorbide A. The present study also demonstrated the potential of pheophorbide A to enhance glucose uptake in β cells. Conclusion The current study’s findings were validated by in-silico and cellular analyses, suggesting that pheophorbide A may regulate GLUT1 and might be regarded as a potential lead for boosting the GSIS pathway, thus maintaining glucose homeostasis.